A Pharmaceutical Study of Rodhradi Lepa - Amonker Rashmina Santosh; Yeriswamy H; Sudhindra A.N; Aditya Arvind Samant (International Journal of Ayurveda and Pharma Research, 2023)
Rodhradi Lepa is a Tarunya Pitikahara Lepa from Gadanigraha Text. It contains Rodhra, Dhatri and Vacha as ingredients. Rodhradi Lepa is a medication applied externally on face (Mukhalepa) for treating Tarunya Pitika (acne). Rodhradi Lepa is in Churna form (powder) which should be mixed with water and applied on face. Preparation of the Churna and Lepa are explained in the Sharangdhara Samhita. In the present study, Churnas of Rodhra (Symplocos racemosa Roxb.), Dhatri (Phyllanthus emblica Linn) and Vacha (Acorus calamus Linn.) were prepared and homogenously mixed to prepare Rodhradi Lepa. Step by step pharmaceutical procedures were carried out according to classical reference and SOP. Loss during the process, total yield is noted. Pharmacological action of the Rodhradi Lepa is discussed In brief.